2016
DOI: 10.1016/j.jpowsour.2016.03.108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of operating conditions on performance of high-temperature polymer electrolyte water electrolyzer

Abstract: Effects of operating conditions of a high-temperature polymer electrolyte water electrolyzer (HT-PEWE) on the electrolysis voltage are evaluated, and the optimal conditions for a high performance are revealed. A HT-PEWE unit cell with a 4-cm 2 electrode consisting of Nafion117-based catalyst-coated membrane with IrO2 and Pt/C as the oxygen and hydrogen evolution catalysts is fabricated, and its electrolysis voltage and high-frequency resistance are assessed. The cell temperature and pressure are controlled at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 30 publications
(30 reference statements)
0
34
0
Order By: Relevance
“…The costs and benefits of a PEMWE operating at high temperature are summarized as follows. An elevated temperature can (1) benefit heat recovery and thermal management, [13] (2) increase the efficiency of energy usage by accelerating the oxygen evolution reaction, [14][15][16][17][18][19][20][21][22][23][24] (3) reduce the amount of noble metal used and thus its cost, [16] and (4) allow for a compact structure for the PEMWE. [17] When the operating temperature increases beyond the boiling point of water, the two-phase flow in the cell will turn into a gas phase flow, which can easily be managed.…”
Section: Body 1 Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The costs and benefits of a PEMWE operating at high temperature are summarized as follows. An elevated temperature can (1) benefit heat recovery and thermal management, [13] (2) increase the efficiency of energy usage by accelerating the oxygen evolution reaction, [14][15][16][17][18][19][20][21][22][23][24] (3) reduce the amount of noble metal used and thus its cost, [16] and (4) allow for a compact structure for the PEMWE. [17] When the operating temperature increases beyond the boiling point of water, the two-phase flow in the cell will turn into a gas phase flow, which can easily be managed.…”
Section: Body 1 Introductionmentioning
confidence: 99%
“…[20][21][22][23][24] Thus, to suppress the dehydration, the cell is pressurized to keep water in the liquid phase rather than in the gas phase. [20][21][22][23][24] However, the elevated pressure then requires a sealing material for the cell and a method to prevent gas leakage. [26] To exploit the advantages of higher temperatures while avoiding membrane dehydration, we propose increasing the temperature up to the boiling point of water.…”
Section: Body 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some authors have investigated the effect of other operating parameters (mainly pressure) on the total system overpotential. Some publications show a positive effect of pressure on performance at 0.6 15 and 2.5 A cm −2 ; 13 other articles show a varied effect of pressure with respect to current density at 1.5, 24 2, 14 and 1 A cm −2 ; 36 further works show a negavite effect of pressure on performance at 1, 35 1.3, 26 1, 31 1.25, 33 and 0.05 mA cm −2 . 40 Another study found an independence between pressure and mass transport losses up until 5 A cm −2 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Electrocatalytic water splitting including two half‐reactions: hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is an efficient reliable technology to achieve mass production of high‐purity hydrogen with low cost and zero emission . The slow kinetics of water splitting and the high overpotentials necessitate high‐performance catalysts to decrease the electrolysis cell voltage and power consumption . However, the platinum‐ and iridium‐based catalysts are still the most active HER and OER catalysts and the low reserves and the high cost limits its application in large‐scale water splitting …”
Section: Introductionmentioning
confidence: 99%